"Back Home You Just Go Talk to the Family": The Role of Family Among Women Who Seek Help for Intimate Partner Violence Pre- and Postresettlement to the United States. Issue 15 (August 2021) - Wachter, Karin; Cook Heffron, Laurie; Dalpe, Jessica
Gaps in knowledge remain regarding how and from whom women resettling to the United States as refugees seek help for intimate partner violence (IPV), and what happens when they do. This study examined ways in which women seek help for IPV across varied contexts and at different times both pre- and postresettlement. Researchers used a purposive sampling approach to recruit women who resettled to the United States as refugees ( n = 35). An inductive approach to thematic analysis led to an examination of the role of family in seeking help for IPV and seeking help in the absence of family. The findings speak to the importance of applying a social support lens to theory, practice, and research concerned with women's help-seeking for IPV in the resettlement context.